ANALISIS USAHA PENANGKARAN BURUNG MURAI BATU (Cophycus malabaricus) DI KABUPATEN OKU TIMUR - Hariyono (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2018)
The purpose of this study is to 1. Know the cost and income of the Murai Batu bird breeding business. 2. Knowing the feasibility level of the Murai Batu bird breeding business. This research was conducted in Sidogede Village, Belitang District and in Bangun Harjo Village, Buay Madang Timur District, East OKU Regency. This research was conducted in 2017. The research method used is the census method of two samples from two populations of stone magpie breeding business in Sidogede Village, Belitang District, East OKU Regency and in Bangun Harjo Village, Buay Madang Timur District, East OKU Regency. The data obtained from the field will be processed tabulated and mathematically, which includes production costs, revenue, income, calculating the R / C ratio, and analyzing financial feasibility. Based on the results of the research that has been done, the following conclusions can be drawn: 1. The amount of income from the magpie bird breeding is Rp. 13,000,000, with a total cost of Rp. 1,301,254.86 so that an income of Rp. 11,689,745.14. 2. NPV (Net Present Value) analysis in the breeding of stone magpies is IDR 813,474,900. With the IRR (Internal rate of Return) value is 71.8%, which means that it is greater than the bank interest rate of 18%, so that the magpie stone breeding business is feasible to be developed. The Net B / C value is 3.26, which is greater than zero, so the business is feasible to develop.